Espaço urbano e criminalidade na região noroeste de Goiânia - GO: a visão dos sujeitos sociais (2004) - Jesus Júnior, Ricardo Sousa de (2005)
The present work has the objective of study de urban space and criminality of the Northwest Region of Goiania, at its inhabitants perspective. This region results from the population that, at the strenth for a home, occupied a part of an abandoned farm aroud the city, at the 70`s, what resulted the political violence. Then the city public power desaproprieted the area, consolidating the urban occupation. Later, this region was abandoned by public power. The increasing number of steals and robs to the people and to the patrimony, the few number of the militar and civilian polices, the use of drugs, and the shortage of political social inclusion, the population`s unhappyness and inphastructure, leisure and culture explain why the Goiania`s Northwest region is, nowadays, the most violent metropolitan region. Here are some alternatives for the fragile citizenship situation, which accepts or make part of the urban violence that characterizes the Northwest region, alterates itself, improving life conditions of the population and modify its inserction in the urban goianiense metropolis.